2021
DOI: 10.1111/andr.13041
|View full text |Cite
|
Sign up to set email alerts
|

The future direction of imaging in prostate cancer: MRI with or without contrast injection

Abstract: Background: Multiparametric MRI (mpMRI) is the "state of the art" management tool for patients with suspicion of prostate cancer (PCa). The role of non-contrast MRI is investigated to move toward a more personalized, less invasive, and highly costeffective PCa diagnostic workup.Objective: To perform a non-systematic review of the existing literature to highlight strength and flaws of performing non-contrast MRI, and to provide a critical overview of the international scientific production on the topic. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 115 publications
0
13
0
Order By: Relevance
“…( 17 ) reported an overall csPCa detection rate of 16–21% based on 665 PI-RADS 3 lesions, consistent with our results. Nevertheless, it is still recommended to use DCE imaging as a supplementary sequence for indeterminate lesions, small cancers, lesions in challenging locations and in previously treated prostates ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 17 ) reported an overall csPCa detection rate of 16–21% based on 665 PI-RADS 3 lesions, consistent with our results. Nevertheless, it is still recommended to use DCE imaging as a supplementary sequence for indeterminate lesions, small cancers, lesions in challenging locations and in previously treated prostates ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Schoots et al (17) reported an overall csPCa detection rate of 16-21% based on 665 PI-RADS 3 lesions, consistent with our results. Nevertheless, it is still recommended to use DCE imaging as a supplementary sequence for indeterminate lesions, small cancers, lesions in challenging locations and in previously treated prostates (18). Although the use of the PI-RADS has widened the application value of prostate MRI, it must be noted that the inter-reader variability remains an unsolved problem.…”
Section: Discussionmentioning
confidence: 99%
“…The shift‐in‐paradigm mentioned above has revealed that a significant number of such lesions are benign 9 . In a similar manner, this has occurred with multiparametric prostate‐MRI, which has significantly changed the indication and need for prostate‐biopsies 10 …”
mentioning
confidence: 82%
“…9 In a similar manner, this has occurred with multiparametric prostate-MRI, which has significantly changed the indication and need for prostate-biopsies. 10 This Special Issue of Andrology brings together excellent research on this topic. The call for papers was launched in 2020 and was characterized by a fast-track phase, gathering manuscripts submitted up to March 30, 2021, followed by rigorous review times, for both authors and reviewers.…”
Section: Imaging Andrology Of the Future: Where Functional Imaging Em...mentioning
confidence: 99%
See 1 more Smart Citation